Aplicación de técnicas de estudio “Leli” para desarrollar las habilidades cognitivas en los estudiantes del 2do grado de secundaria de la I.E Santo Toribio - Garcia Tapullima, Lincoln (2010)
The present work of investigation called technologies of study-leli to develop the cognitive skills of the students of the second degree of secondary education in the area of science and technology and environment - sub. component Physical World, Technology and Environment, 1 develop in the educational institution Saint Toribio, located in the district and province of Rioja, department of san Martin. In the logical structure, and component took as a reference the problems of learning demonstrated in the sub. Physical World, Technology and Environment, correspondent to the area of science and technology and environment, which 1 constitute the central problem of the investigation. In this perspectiva, there objective general facilitate the development of the cognitive skills in the students of the second degree, for which 1 apply the technologies of study to them with the intention of improving the above mentioned skills for a better learning of natural ciencias, which 1 constitute the central hypothesis of the investigation research. In the operative part, the investigation was led under the design cuasi experimentally, with a group control shaped by 35 pupils and an experimental group shaped by 35 pupils. T o confirm the hypothesis ene u sed the distribution t - student, by means of a unilateral test with a confidence level of 95 % arriving at the conclusion that the correct application of the technologies of studies "LELI" facilitate significantly the cognitive skills in the students of the second degree of secondary education in the area of science technology and environment - component physical world technology and environment, Likewise also 1 demonstrate that the pupils of the experimental group managed they will improve all that to capacities of attention, comprehension, elaboration and memorization, with which 1 remain completely demonstrated the hypothesis of investigation.